2011
DOI: 10.1080/17470919.2010.513495
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of mindfulness: An fMRI investigation

Abstract: "Mindfulness" is a capacity for heightened present-moment awareness that we all possess to a greater or lesser extent. Enhancing this capacity through training has been shown to alleviate stress and promote physical and mental well-being. As a consequence, interest in mindfulness is growing and so is the need to better understand it. This study employed functional magnetic resonance imaging (fMRI) to identify the brain regions involved in state mindfulness and to shed light on its mechanisms of action. Signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 50 publications
2
73
0
6
Order By: Relevance
“…This suggests an increased awareness of internal state (87) . In another study, fMRI results showed reduced activation in the insula (88) which is the part of the cerebral cortex implicated in self-awareness and perception and hence is linked with interoceptive awareness.…”
Section: Potential Associated Mechanismsmentioning
confidence: 99%
“…This suggests an increased awareness of internal state (87) . In another study, fMRI results showed reduced activation in the insula (88) which is the part of the cerebral cortex implicated in self-awareness and perception and hence is linked with interoceptive awareness.…”
Section: Potential Associated Mechanismsmentioning
confidence: 99%
“…Another body of research examined functional neural differences between mindfulness practitioners with significant meditation experience (i.e., several years of daily practice) and meditation naïve controls matched on variables such as age, sex, education, and handedness (Brewer et al, 2011;Hölzel et al, 2007;Ives-Deliperi, Solms, & Meintjes, 2011;Taylor et al, 2011;Wang et al, 2011). One study compared neural processing of emotionally evocative images in meditation naïve participants and meditators with over 1,000 hours of zen meditation experience under mindful viewing instruction and no instruction conditions (Taylor et al, 2011).…”
Section: State Mindfulness Research In Experienced Meditatorsmentioning
confidence: 99%
“…Specifically, during the practice of mindfulness, taskspecific activation occurs in a constellation of medial structures that subserve reflective function and interoception (e.g., the anterior insula, ACC, medial prefrontal cortex, and bilateral precuneus) (Ives-Deliperi et al 2011). Functional magnetic resonance imaging (fMRI) studies in subjects with affective and anxiety disorders, as well as in healthy subjects, reveal treatment-related effects of MBCT.…”
Section: Introductionmentioning
confidence: 99%